La competitividad y los emprendimientos de ropa y calzado de la ciudad de Santo Domingo de los Tsáchilas. - Intriago Cedeño, Mishell Nicole (2023)
Competitiveness in clothing and footwear enterprises in the city of Santo Domingo de los Tsachilas is an important factor on which these ventures are based on the improvement of their market positioning and productivity. Industry strategies give entrepreneurship an edge over other firms with the same product. For the purpose that competitiveness strategies generate the expected results in clothing and footwear ventures in the city some objectives and hypotheses were raised in this research work in order to help with the determination of the study. In the theoretical section, the variables are described, giving us the knowledge needed to develop competitiveness strategies. In the methodological section, the hypothetical-deductive method was chosen, which makes it possible to verify or deny the proposed assumptions, to collect, analyze the data and to give results. The field and descriptive research were used, which enabled us to study the phenomenon of research and to resolve the problem raised in this research. In the section of the surveys, the levels of competitiveness of the clothing and footwear enterprises of the city of Santo Domingo de los Tsáchilas, the productivity, quality and aspirations of these enterprises are analyzed. The strategies proposed in chapter 6 are based on the positioning, loyalty of the brand, creation of opportunities, commercial growth, seeking the improvement of the clothing and footwear enterprises of the city of Santo Domingo de los Tsáchilas.